Decisional issues in antibiotic prescribing in French nursing homes: An ethnographic study - Taghrid Chaaban; Mathieu Ahouah; Pierre Lombrail; Hélene Le Febvre; Adnan Mourad; Jean-Manuel Morvillers; Monique Rothan-Tondeur (SAGE Publishing, 2019)
Background: Medication prescription is generally the responsibility of doctors. In nursing homes, the nursing staff is often the first to suspect an infection. Today, physicians are more confident with nursing assessment, relying primarily on nursing staff information. Very few studies have investigated the nurses' influence on decision of medical prescription. This study investigates the role of nurses in antibiotic prescribing for the treatment of suspected infections in nursing home residents. Design and methods: An ethnographic study based on semi-structured interviews and participant observations was conducted. Sixteen nurses and five doctors working in five nursing homes in Paris, France participated between October 2015 and January 2016. Results: Given their proximity to elderly residents, registered nurses at the nursing homes occasionally assisted doctors in their medical diagnostic. However, nurses who are theoretically incompetent have met difficulties in their ability to participate in their decisions to prescribe antibiotics when managing residents' infections. Conclusion: if proximity and nursing skills reinforce the relevance of the clinical judgment of nurses, the effective and collaborative communication between the nurse and the doctor may help the nurse to enhance their role in the antibiotic prescribing in nursing homes, which would enhance antimicrobial stewardship efficiency.